1994
DOI: 10.1093/nar/22.23.4914
|View full text |Cite
|
Sign up to set email alerts
|

Different members of the Sp1 multigene family exert opposite transcritional regulation of the long terminal repeat of HIV-1

Abstract: Recently, a family of transcription factors structurally related to Sp1 has been described; thus, more than one activator may bind to the GC boxes present in a number of viral and cellular promoters. We have compared the transactivation potentials of Sp1, Sp3 and Sp4 proteins on the human immunodeficiency virus type 1 (HIV-1) promoter. The long terminal repeat (LTR) of HIV-1 contains three binding sites for the transcription factor Sp1 (GC boxes) which are involved in both basal and Tat-mediated transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
234
3
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(263 citation statements)
references
References 31 publications
24
234
3
2
Order By: Relevance
“…A three zinc finger domain is highly conserved in members of this family, resulting in similar binding affinities to GC, GT and GA boxes. Sp1, Sp2 and Sp4 activate gene transcription, whereas Sp3 may function either as an activator or a repressor (49)(50)(51)(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…A three zinc finger domain is highly conserved in members of this family, resulting in similar binding affinities to GC, GT and GA boxes. Sp1, Sp2 and Sp4 activate gene transcription, whereas Sp3 may function either as an activator or a repressor (49)(50)(51)(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…Sp3 has been reported to repress Sp1-mediated transcriptional activation, suggesting that it may be an inhibitory member of the Sp family of regulators (Majello et al, 1994;Hagen et al, 1995). However, the recent ®nding that Sp1 and Sp3 encode multiple proteins that di er in their capacity to stimulate or repress transcription, suggests that transcriptional control by the Sp family members is much more complex (Persengiev et al, 1995;Kennett et al, 1997;Dennig et al, 1997).…”
Section: Cooperation Of P300 and Sp1 In Cell Cycle Arrest During DI Ementioning
confidence: 99%
“…Two Sp3-related proteins of 78 kDa and 80 kDa, arising via internal translational initiation within Sp3 mRNA, have been described (Kennett et al, 1997). These two isoforms inhibit Spmediated transcription in vivo, while the initially described 110 kDa isoform behaves as a transcriptional activator (Majello et al, 1994). In the present study, we observed that all three isoforms of Sp3 are present in PC12 cells and speci®cally associate with the NGF-responsive region of the p21 promoter in both NGF-treated and exponentially-growing PC12 cells.…”
Section: Cooperation Of P300 and Sp1 In Cell Cycle Arrest During DI Ementioning
confidence: 99%
“…Sp2, Sp3 and Sp4 are Sp1-related proteins. These proteins, like Sp1, are ubiquitously expressed, are glutamine-and serine/threonine-rich, and have similar DNA-binding speci®city, but display di erential e ects on the gene regulation (Hagen et al, 1992Kingsley and Winoto, 1992;Majello et al, 1994;Dennig et al, 1995). Among these, Sp1 is a highly studied factor and is known to activate many GC-box-containing viral and cellular promoters Tjian, 1983a,b, 1985;Gidoni et al, 1985).…”
Section: Introductionmentioning
confidence: 99%